2012
DOI: 10.1016/j.gie.2011.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic pancreatic function test using combined secretin and cholecystokinin stimulation for the evaluation of chronic pancreatitis

Abstract: Background Current endoscopic pancreatic function test (ePFT) methods use either secretin or cholecystokinin (CCK) to measure pancreatic function. Objective Evaluate a novel ePFT protocol that includes both secretin and CCK stimulation, and assess which fluid parameters best discriminate patients with chronic pancreatitis (CP). Design Prospective, cross-sectional diagnostic study. Setting Single, tertiary-care institution. Patients and interventions Healthy volunteers and patients evaluated for CP were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…There is significant variability and error with this test, and it has largely been replaced. The secretin‐cholecystokinin (CCK) stimulation test is a direct measure of pancreatic function and is the current gold standard for diagnosis . The secretin‐CCK test is a combination of 2 tests—the secretin test, which measures pancreatic ductal cell bicarbonate and fluid secretion, and the CCK test, which measures pancreatic acinar cell enzyme secretion.…”
Section: Malnutrition Associated With Chronic Pancreatitismentioning
confidence: 99%
“…There is significant variability and error with this test, and it has largely been replaced. The secretin‐cholecystokinin (CCK) stimulation test is a direct measure of pancreatic function and is the current gold standard for diagnosis . The secretin‐CCK test is a combination of 2 tests—the secretin test, which measures pancreatic ductal cell bicarbonate and fluid secretion, and the CCK test, which measures pancreatic acinar cell enzyme secretion.…”
Section: Malnutrition Associated With Chronic Pancreatitismentioning
confidence: 99%
“…Several variations of direct PFTs using endoscopy have been described including the use of secretin and/ or CCK [10][11][12][13][14][15]. Rather than using an enteric tube, duodenal lumen contents are aspirated through the accessory channel of the endoscope.…”
Section: Direct Pancreas Function Testingmentioning
confidence: 99%
“…Even though this measurement is more directly a measure of pancreatic duct epithelial cell function than acinar cell function, previous studies have demonstrated a correlation between the peak bicarbonate and lipase concentrations in pancreatic fluid (3). For the evaluation of CP, measurement of peak bicarbonate concentration (following secretin stimulation) has improved discrimination compared with peak lipase or amylase concentrations following cholecystokinin stimulation (4). Notably, a retrospective follow-up study demonstrated that the negative predictive value of a normal bicarbonate response to secretin stimulation to rule out CP is high (97%), while the positive predictive value (45%) is poor (5).…”
Section: Clinical Indications For Pancreatic Fluid Collectionmentioning
confidence: 99%
“…However, it is necessary to utilize standardized methodology for PF collection to ensure that downstream analyses are accurate and reproducible. We set out to: (1) review the clinical role of ePFT, (2) discuss the current methodology for endoscopic PF collection, (3) review preliminary observations demonstrating opportunities for future translational research, and (4) to identify gaps in knowledge.…”
Section: Introductionmentioning
confidence: 99%